Emerging patterns of resistance in a cohort of Greek patients with recurrent UTIs: a pilot study. (17th November 2019) - Moustakas, Ioannis; Dryllis, Georgios; Pouliakis, Avraham; Petrikos, Georgios; Daikos, Georgios; Pittaras, Theodoros; Karasante, Panagiota; Karampotsis, Konstantinos; Tsiodras, Sotirios
Abstract : Bacterial urogenital infections caused by multi-drug resistant organisms (MDROs), are increasingly becoming a severe public health issue. The purpose of the present study was to examine the epidemiology of recurrent UTIs along with antimicrobial resistance patterns in a cohort of patients followed as outpatients at an Infectious Disease clinic of a tertiary care center in Greece. One hundred, sequential patients suffering from recurrent UTIs and coming for clinical evaluation, follow-up and treatment were examined; microbiological urine culture results were analyzed. Patients were separated into Group A: patients with ≥3 urogenital infections during the last study year, and Group B: patients with ≤2 urogenital infections. Furthermore, antimicrobial resistance patterns and presence of MDROs in relation to the number of urogenital infections during a three years period was evaluated. Group A had a mean of 4.3 ± 1.7 urogenital infections during the last year of the study, while patients in Group B 1.9 ± 0.3 infections over a three years period. An age cut-off of 30 years was critical for higher UTI rates. Escherichia Coli was the predominant isolated pathogen in 96.2% of the patients. Patients with diabetes mellitus had a 3 fold-higher risk for ≥3 UTIs. Resistance to colistin and imipenem was associated with a history of more than 2 episodes of UTIs but observed in a small number of patients with comorbidities. In this pilot study MDRO detection in patients suffering from recurrent UTIs emphasizes the need for continuous epidemiological surveillance in order to improve our understanding of the evolution of resistance in a common community infection as well as to implement successful prevention strategies.